P348 Correlation between Mayo endoscopic score and validated histological score in ulcerative colitis. (25th January 2019) - Shah, J; Dutta, U; Das, A; Sharma, V; Madhavdhare, H; Dhaka, N; Sinha, S K; Kochhar, R
Abstract: Background: Mayo Endoscopic Score (MES) remains the most commonly used index in routine practice and various clinical trials. Recently two histological indices (Nancy and Robert Histological Index) have been developed in UC. Correlation between MES and these two validated histological scores has not been established. We aim to correlate MES with two validated histological indices in patients with UC. Methods: It was a prospective single-centre study. Ninety-six patients with UC with different levels of severity were included. MES was documented from the most affected area. Biopsy was taken from the same area and reported by single gastrointestinal histopathologist who was blinded to the endoscopic score. Histological activity was reported using Nancy Index (NI) and Roberts Histological index (RHI). Statistical analysis was performed using Spearman's correlation coefficient and kappa coefficient. Results: In total, 96 patients with UC, with median age of 36 years were enrolled. Seventeen patients were in endoscopic remission (MES 0/1). Correlation coefficient between MES and NI was r = 0.389 ( p < 0.001) and correlation coefficient between MES and RHI was r = 0.442 ( p < 0.001). There was an excellent correlation between NI and RHI r = 0.872 ( p < 0.001). In patient with endoscopic mucosal healing ( n = 17), agreement coefficient between MES and RHI was k = 0.336 ( p = 0.001) and agreement coefficient between MES and NI was k = 0.053 ( p = 0.573). Conclusions: Mayo endoscopic score only moderately correlate with NI and RHI. Endoscopic mucosal healing is not strongly correlated with histological healing. Histological examination should be performed even in patients with mucosal healing to detect ongoing histological activity